Thermo-economic optimization in the design of small-scale and residential cogeneration systems - Leão, Celina Pinto (2009)
n recent years, gas-turbine engines have undergone major improvements both in efficiency and cost reductions. Several inexpensive models are available in the range of 30 to 250 kWe, with electrical efficiencies already approaching 30%, due to the use of a basic air-compressor associated to an internal air pre- heater. Gas-turbine engines offer significant advantages over Diesel or IC engines, particularly when Natural Gas (NG) is used as fuel. With the current market trends toward Distributed Generation (DG) and the increased substitution of boilers by NG-fuelled cogeneration installations for CO2 emissions reduction, small-scale gas turbine units can be the ideal solution for energy systems located in urban areas. A numerical optimization method was applied to a small- scale unit delivering 100 kW of power and 0.86 kg/s of water, heated from 318 to 353K. In this academic study, the unit is based on a micro gas-turbine and includes an internal pre- heater, typical of these low pressure-ratio turbines, and an external heat recovery system. The problem was formulated as a non-linear optimisation model with the minimisation of costs subject to the physical and thermodynamic constraints. Despite difficulties in obtaining data for some of the components cost- equations, the preliminary results indicate that the optimal compressor pressure ratio is about half of the usual values found in large installations, but higher than those of the currently available micro-turbine models, while the turbine inlet temperature remains virtually unchanged.